(untitled) (International Journal of Engineering and Computer Science, 2017)
Designers of systems have always been deeply concerned about their systems demise. The idea address some thoughts on the implementation of ODA Link systems, particularly with respect to processing design platform that remain malleable and stable through periods of experimentation and radical change. When documents are to be accessed the link structure of the documents should be employed. The structures also form the basis for the presentation of the content of the document to the user. The content of document is not just text but a highly structured collection of text fragments and figures. The model defines link to capture relations and consists of specifications of its starting point and its ending point. The link context structure defines that the displayed component should only be replaced when it is not the component the activated link is pointing to.